Technology Transfer - Magdalena Klimczuk-Kochańska; Andrzej Klimczuk (The SAGE Encyclopedia of World Poverty, 2015)
Technology transfer is the movement of technical and organizational skills, knowledge, and methods from one individual or organization to another for economic purposes. This process usually involves a group that possesses specialized technical skills and technology that transfers it to a target group of receptors who do not possess those skills, and who cannot create that technology themselves.
Keywords: O33; 300; Financing New Technology; High Technology and International Trade; International Trade; Technology Diffusion